Building The Learning Organization Based On Marquardt,s Model In Shahrekord University Of Medical Sciences - Mahdi Sattari-Ghahfarrokhi; Mehdi Abzari (Tehran University of Medical Sciences, 2012)
Background and Aim: Learning may be the only sustainable competitive advantage for all organizations. A learning organization is an organisation where people continually expand their capacity to create results they truly desire new and expansive patterns of thinking are nurtured collective aspirations are set free people are continually learning from what others have learned. The aim of this research is to study whether a learning organization and its subsystems are established in Shahrekord University of Medical Sciences (SKUMS). Materials and Methods: This descriptive-survey study was conducted in 2012. Marquardt's standard questionnaire was used to measure learning organization based on Likert's scale with a Cronbach's Alpha coefficient of 0.946. The research sample consisted of 177 staff members (bachelor's degree holders and bove) in seven vice-chancellorships of SKUMS, selected through simple random sampling. Results: The findings of the study are twofold. (1) According to the results of one-sample t-test with a 95% confidence interval, the mean scores in learning organization and sub-systems of learning dynamics, people empowerment, knowledge management and technology application subsysems were higher than the assumed mean of 3 however, the figure turned out to be equal to the assumed mean for the organization transformation subsystem, and (2) Based on Freidman Test, there was a significant difference between the means of at least 2 learning organization subsystems. Conclusion: According to the research findings, more attention should be paid to the subsystems of learning organization establishment and balanced development of these subsystems.